1983
DOI: 10.1021/es00112a011
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and chemical analysis of interstitial water from soils and rocks

Abstract: Interstitial water was extracted from field-moist soils and chalk by immiscible displacement with a dense, inert fluorocarbon liquid. The only special equipment required is a high-speed centrifuge. Yields of interstitial water from soils at field capacity are typically 20-50% of the total water present; yields from chalk range up to 90%. The interstitial water was analyzed for about 20 solutes principally by inductively coupled plasma emission spectrometry. The water extracted from a chalk sample appeared to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
0

Year Published

1984
1984
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(70 citation statements)
references
References 12 publications
0
70
0
Order By: Relevance
“…Each sample consisted of ~1.5 kg of a bulked sample from five 10 sub-samples collected at the corners and the centre of a 5 m 2 grid. A portion of soil was used to extract > 30mL pore water using quartz filters and following the centrifugation method of Kinniburgh and Miles 42 . Pore waters were filtered and kept for further analysis of non-purgeable organic carbon (NPOC), major 15 and trace elements, major anions and pH.…”
Section: Soil and Soil Pore Water Collectionmentioning
confidence: 99%
“…Each sample consisted of ~1.5 kg of a bulked sample from five 10 sub-samples collected at the corners and the centre of a 5 m 2 grid. A portion of soil was used to extract > 30mL pore water using quartz filters and following the centrifugation method of Kinniburgh and Miles 42 . Pore waters were filtered and kept for further analysis of non-purgeable organic carbon (NPOC), major 15 and trace elements, major anions and pH.…”
Section: Soil and Soil Pore Water Collectionmentioning
confidence: 99%
“…All analyses were blank corrected and detection limits defined as 6 times the standard deviation of the blank. Nitrate-nitrogen (NO 3 -N), ammonium-nitrogen (NH 4 -N), and Cl were determined using standard Auto Analyser II colorimetric methods (Kinniburgh and Miles, 1983) on the filtered, unacidified water fraction. Nitrate-nitrogen was determined by the cadmium column reduction method since the high dissolved organic carbon content of the samples can cause suppression of the baseline when the hydrazine/copper reduction method is used.…”
Section: Soil Characterisation and Chemical Analysismentioning
confidence: 99%
“…With the assumption that every centrifugation speed represents a certain pore size and the represented pore size decreases with increasing centrifugation speed [51], it can be concluded that the pore size distribution changed significantly during peat hydration. This change was slow and takes place in two phases.…”
Section: Water Distribution Versus Centrifugation Speedmentioning
confidence: 99%
“…The first phase started very soon after water addition and lasted for more than two days. It was characterised by the decrease of the number of very large pores (> 50 m) represented by centrifugation speeds of 500RPM and the evolution of medium-sized pores 50 -10 m [51], represented by centrifugation speeds of up to 1000 RPM. The second phase started anytime after the first two days of hydration and resulted in the ongoing evolution of medium-sized pores 50 -10 m as well as of small-sized pores 10 -1 m [51], represented by centrifugation speeds of 1000 -4000 RPM.…”
Section: Water Distribution Versus Centrifugation Speedmentioning
confidence: 99%